The effects of two bone substitute materials in the treatment of experimentally induced mandibular defects: An experimental study - Atalla F Rejab (University of Mosul, College of Dentistry, 2018)
Abstract Aims: To compare between the effects of deproteinized bovine bone (DBB) and osteon in the healing of mandibular bone defects in the rabbits. Materials and Methods: This experimental study was conducted on ten rabbits at the Animal House, Dentistry college, Mosul University. The rabbits weighted between 1.5 and 2 kg and each rabbit was given anesthesia (10% ketamine (40 mg/kg) and 2% xylazine (5 mg/kg). Surgery was performed aseptically. Mandibles were exposed through a sub-mandibular incisions. Three rectangular full thickness defects (6×5 mm) were created in each side. The first defect in each side was filled with DBB, the second defect was filled with osteon, while the third defect was left untreated to serve as a control. Five rabbits were sacrificed after one week and the other five rabbits were sacrificed after one month. The bony mandibles were immersed in 10% formalin solution and examined histologically by two histopathologists. Results: Microscopically, sections for one week of all groups showed mild degree of inflammation, moderate amount of vascularity, granulation tissue and osteoid tissue formation. Sections of one month showed no difference regarding the degree of inflammation vascularity, but the amount of granulation tissue and osteoid tissue formation in the control group were lesser than the amount seen in both experimental groups. Conclusions: DBB and osteon accelerate bone healing after month regarding the amount of granulation tissue and osteoid tissue formation.